Géomorphologie : géographie globale – géographie totale – associations internationales - Hamelin, Louis-Edmond (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1964)
The great advances that geomorphology has made in recent years make necessary a critical re-examination of the relationships between this science and the field of geography. Is geomorphology truly geographical ? And if not, how can it become so ?Geomorphology has its roots in geology and was, of course, not designed to meet the specific needs of geographers. Under the leadership of W. M. Davis, geographers eventually adopted the study of geomorphology but did Utile to adapt it to particular purposes of their discipline. Most geographers can never aspire to true excellence in geomorphology because of their generally inadequate training in the physical sciences. We have found that most geographers tend to fall into one of four groups : 1. Those who consider themselves to be geomorphologists (about one-fourth of all geographers) ;2. Those who just try to be informed in geomorphology ;3. Those who ignore the existence of geomorphology ;4. The « complete » geographer who practices a « functional » geomorphology. It also appears that the majority of geographers do not consider land-man relations to be their principal field of interest. The definition that we as geographers give to geography tends to sanction the kind of geography that we are capable of doing. For example, the classical géographie globale, which is characterized by an explanatory description of a complex of physical and human eclectic elements, does not normally require either a « complete » or a genetic geomorphology ; also, complex techniques of geomorphological investigation are not essential. Of greater importance is a geomorphology'-which is functional to geography and which will help us to understand better man's distribution and activities on the surface of the earth. This partial or « functional » geomorphology has achieved its greatest development in France (as an integral part of géographie globale) and is practised by a large number of geographers. Géographie totale, an expression which refers more to the subject matter of this geography than to its methodology, is an ensemble of specialized yet inter-related disciplines (one of which is geomorphology). This pluralistic geography daims many more adherents than does géographie globale. Géographie totale allows us to study all aspects of what is now called geomorphology (but which may eventually be termed « cosmomorphology  »). This new geomorphology is based on geophysical laws and is strictly quantitative. It is an integral part of the physical sciences but this does not mean that it is automatically divorced from man. Scientists of both the United States and the U. S. S. R. are actively engaged in this new geomorphology. We believe that it would be mutually advantageous for both the « functional » and the « complete » geomorphologists to group themselves into a new international association. To achieve this end we urge that the structures of the international Geographical Union be modified or that an « International Association of Geomorphology » be founded.